Analisis Sentimen Terhadap Pelayanan TransJakarta Berdasarkan Tweets Menggunakan Metode Naïve Bayes Classifier - Muflih, Hilmy Zhafran; Hasan, Firman Noor (STMIK Budi Darma, 2024)
The high use of private transportation in Indonesia, especially in the Jakarta area, causes several impacts, one of which is traffic jams. This congestion condition can be reduced by public transportation. It is hoped that public transportation can now reduce the level of congestion in Jakarta. One of the public transportation in Jakarta is TransJakarta. TransJakarta is a form of transportation that can carry a relatively large number of passengers and TransJakarta offers various facilities to users, such as the availability of priority seating, stops that are quite comfortable, comfortable conditions on the bus plus low prices so that it gets various responses from users who led researchers to conduct research on the views of TransJakarta users regarding TransJakarta services, whether TransJakarta users' responses were positive or negative. The purpose of this research is to understand whether users are satisfied or not with the services provided by TransJakarta. The method used in the research is the Naïve Bayes Classifier algorithm which is used to carry out the sentiment analysis process regarding TransJakarta services with the help of the RapidMiner application. The data collected by researchers was 773 tweet data obtained via social media X to be used as a dataset. The results of sentiment analysis from the Naïve Bayes Classifier algorithm obtained 80.6% or 623 negative sentiments and 19.4% or 150 positive sentiments from 773 datasets. The results of the confusion matrix evaluation obtained an accuracy value of 73.96%.